IMPLEMENTASI MOTIVASI GURU DALAM MEWUJUDKAN KINERJA GURU DI SDN DERMO I BANGIL - Yuli Wariyanti; Sutinah; Niken Muji Suryaningsih; Eko Budi Setyawan; A. Faizin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the implementation of teacher motivation in realizing professional performance at SDN Dermo I Bangil and to understand the factors influencing teachers’ work enthusiasm and commitment within the context of elementary education. The phenomenon of declining teacher performance in several primary schools has become a crucial issue closely related to the quality of motivation and institutional support. This research employs a qualitative approach with an intrinsic case study design, focusing on an in-depth understanding of teachers’ lived experiences within their real work environment. Data were collected through semi-structured interviews, participatory observation, and document analysis, involving three key informants: a classroom teacher, an Islamic education teacher, and a physical education teacher, selected through purposive sampling. The findings reveal three main themes: (1) motivation as a calling of service, where teachers are driven by spiritual values and moral responsibility; (2) motivation based on workplace support, including principal appreciation, peer collaboration, and harmonious social relationships; and (3) motivation transforming into professional performance, manifested through self-reflection, instructional innovation, and commitment to student development. The main inhibiting factors include administrative workload, limited facilities, and lack of professional recognition. The study provides a theoretical contribution by enriching the Self-Determination Theory within Indonesia’s elementary education context and a practical implication for policymakers to enhance teacher well-being and motivation through non-material rewards, organizational support, and reflective professional practices. Future studies are recommended to expand cross-school research and adopt a longitudinal approach to better understand the dynamics of teacher motivation over time.